OA03.02. The effect of kutaja pratisaraniya kshara in the management of ardra arshas. - Pathak, Avnish (Medknow Publications & Media Pvt Ltd, 2013)
PURPOSE: To evaluate the effect of Kutaja Pratisaraniya Kshara and Apamarga Pratisaraniya Kshara in the management of Ardra Arshas and to compare the effect of both the Groups. METHOD: Cases presenting with classical signs and symptoms of Ardra Arshas were selected and randomly allocated into two groups i.e. GroupA and GroupB. In GroupA Apamarga Pratisaraniya Kshara was applied and in GroupB Kutaja Pratisaraniya Kshara was applied. The signs and symptoms of Ardra Arshas i.e. bleeding per rectum, pain, defecation, tonicity of anal sphincter, sloughing of the pile mass and size of Arshas was assessed before and after the completion of treatment. RESULT: After the 30 days of treatment with Kutaja Pratisaraniya Kshara provided significant relief in pain by 100%, in bleeding by 97.61%, in defecation 100%, slough by 100%, in colour of pile mass by 98.33%. in tonicity of the anal canal by 95% and in size of pile mass by 98.33%, and no recurrence noticed. After the 30 days treatment with Apamarga Pratisaraniya Kshara provided significant relief in pain by 100%, in bleeding by 97.7%, in defecation 95.5, in slough by 100%, in colour of pile mass by 98.1%. in tonicity of the anal canal by 95.2% and in size of pile mass by 96.6% and no recurrence noticed. On the basis of comparison of the effects as mentioned above it can be said that the application of Kutaja Kshara provided better relief in pain, defecation, slough and size of the pile mass of the patients in comparison to Apamarga Kshara. CONCLUSION: Group B cases showed better improvement when compared to Group A However all 20 cases of Group A and 20 cases of Group B showed good results.